Student Data Report, Oklahoma Higher Education, 1984-85 - Oklahoma State Regents for Higher Education, Oklahoma City.; Oklahoma State Regents for Higher Education, Oklahoma City. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The 1984-1985 Student Data Report, which is derived from the Oklahoma Regents' Unitized Data System, is presented. Statistical data and narrative sections cover movement into college, enrollments, student distribution, student progression, and transfer of students. Specific topics include: average annual movement of Oklahoma students into college from high school; high school senior and first-time freshmen enrollments by county; first-time freshmen enrollment (comparison with the previous year); headcount enrollment by class level; enrollment by division; student semester hours by division; enrollment by race, sex, class level, and full-time/part-time status; unduplicated headcount student enrollments for public schools by race and sex; percentage of student enrollment by race within the institution; percentage of student enrollment by race within the state system; public and private enrollments by program of study and class level; public enrollments by county; public college enrollment by age, sex, race, and class level; public undergraduate study progression; transfer pattern of students; distribution of financial aid dollars; and financial aid by institution. Findings from the summary include: 45% of the enrollment were 25 years old and older, and 45% were enrolled part-time. (SW)
Availability: Oklahoma State Regents for Higher Education, 500 Education Building, State Capitol Complex, Oklahoma City, OK 73105.
ERIC Note: For an earlier report, see ED 256 283.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Persistence; Age Groups; College Freshmen; College Students; College Transfer Students; Comparative Analysis; Enrollment Trends; Females; Higher Education; Majors (Students); Males; Place of Residence; Private Colleges; Racial Distribution; State Colleges; State Surveys; Student Characteristics; Oklahoma; Numerical/Quantitative Data; Reports, Descriptive